ANALISIS SIKAP NASABAH TERHADAP PERBANKAN SYARIAH DI SUMATERA BARAT - RONI ANDESPA (Maqdis: Jurnal Kajian Ekonomi Islam, 2018)
The theme of the research is: sharia business management. The objective of this research is to analyze customer attitude toward syariah bank in West Sumatera. The object of research is sharia bank in West Sumatra. The variables studied were: administrative cost, service, service diversity and location. The sample of research is 100 customer. Data analysis using fishbein analysis. The result of research is: customer attitude toward syariah bank is good enough to attribute in the form of price, service, service diversity and location. This can be seen from the total index of attitudes obtained that is equal to 53.9992. The service attribute has the largest attitude index, with the value of 16.1435, while the location attribute has the smallest index that is 11.8012. Thus, service attributes have the greatest contribution in determining the attitude of customers to sharia banks.